Collegiate athletes` cognitive beliefs related to setback anxiety and rumination in sport - Parker, P. C.; Daniels, L. M.; Mosewich, A. D. (Research Quarterly for Exercise and Sport, 2024)
Setbacks are common occurrences in sport. Recently, setbacks such as injuries and deselection have been accompanied, and confounded, by setbacks related to COVID-19. How students manage a setback may depend on the interaction of two control beliefs: primary control (PC) to directly influence the setback and secondary control (SC) to adjust to it.